Fungicide exposure accelerated horizontal transfer of antibiotic resistance genes via plasmid-mediated conjugation. (15th April 2023) - Zhang, Houpu; Song, Jiajin; Zheng, Zhiruo; Li, Tongxin; Shi, Nan; Han, Yuling; Zhang, Luqing; Yu, Yunlong; Fang, Hua
Highlights: Agricultural fungicides facilitated horizontal transfer of ARGs via conjugation. The promoting conjugation of ARGs depended on specific fungicide and donor/recipient. Chlorothalonil exposure increased SOS response and cell membrane permeability. Azoxystrobin and carbendazim enhanced the expression of conjugation-related genes. Abstract: Co-pollution of soil with pesticide residues and antibiotic resistance genes (ARGs) is increasing due to the substantial usage of pesticides and organic fertilizers in greenhouse-based agricultural production. Non-antibiotic stresses, including those from agricultural fungicides, are potential co-selectors for the horizontal transfer of ARGs, but the underlying mechanism remains unclear. Intragenus and intergenus conjugative transfer systems of the antibiotic resistant plasmid RP4 were established to examine conjugative transfer frequency under stress from four widely used fungicides: triadimefon, chlorothalonil, azoxystrobin, and carbendazim. The mechanisms were elucidated at the cellular and molecular levels using transmission electron microscopy, flow cytometry, RT-qPCR, and RNA-seq techniques. The conjugative transfer frequency of plasmid RP4 between Escherichia coli strains increased with the rising exposure concentrations of chlorothalonil, azoxystrobin, and carbendazim, but was suppressed between E. coli and Pseudomonas putida by a high fungicide concentration (10 µg/mL). Triadimefon did not significantly affect conjugative transfer frequency. Exploration of the underlying mechanisms revealed that: (i) chlorothalonil exposure mainly promoted generation of intracellular reactive oxygen species, stimulated the SOS response, and increased cell membrane permeability, while (ii) azoxystrobin and carbendazim primarily enhanced expression of conjugation-related genes on the plasmid. These findings reveal the fungicide-triggered mechanisms associated with plasmid conjugation and highlight the potential role of non-bactericidal pesticides on the dissemination of ARGs. Graphical abstract: Image, graphical abstract